Deciphering Neuroprotective Effect of Rosmarinus officinalis L. (syn. Salvia rosmarinus Spenn.) through Preclinical and Clinical Studies - Oresanya, Ibukun O.; Orhan, Ilkay E. (Current Drug Targets, 2024)
Rosmarinus officinalis L. (RO, rosemary) is a well-known medicinal, aromatic, and culinary herb with traditional use in European folk medicine against memory deficits and neurodegenerative disorders. This review highlights the different neuroprotective activities of RO investigated in both preclinical and clinical studies, as well as in silico molecular docking of bioactive compounds found in RO. The neuroprotective effect of RO was searched through databases including PubMed, Web of Science (WoS), Scopus, and Clinical Trials using the keywords “Rosmarinus officinalis, rosemary, neuroprotective effect, memory, cognitive dysfunction, Alzheimer's disease.” RO, which is rich in secondary metabolites that have memory-enhancing potential, has displayed neuroprotection through different molecular mechanisms such as inhibition of cholinesterase, modulation of dopaminergic and oxytocinergic systems, mediation of oxidative and inflammatory proteins, involved in neuropathic pain, among others. RO extracts exhibited antidepressant and anxiolytic activities. Also, the plant has shown efficacy in scopolamine-, lipopolysaccharide-, AlCl3-, and H2O2-induced amnesia as well as amyloid-beta- and ibotenic acid-induced neurotoxicity and chronic constriction injury-related oxidative stress memory and cognitive impairments in animal models. A few clinical studies available supported the neuroprotective effects of RO and its constituents. However, more clinical studies are needed to confirm results from preclinical studies further and should include not only placebo-controlled studies but also studies including positive controls using approved drugs. Many studies underlined that constituents of RO may have the potential for developing drug candidates against Alzheimer’s disease that possess high bioavailability, low toxicity, and enhanced penetration to CNS, as revealed from the experimental and molecular docking analysis.
Keywords: cognition improvement